APPROACHES TO DEVELOPING A STRATEGIC PROGRAM FOR HIGH-TECH ENTERPRISE IN THE CONTEXT OF DIGITAL TRANSFORMATION - Novikov, Sergey; Sazonov, Andrey (Journal of Applied Engineering Science, 2021)
The article is devoted to the consideration of approaches to the development of a strategic program for the development of high-tech enterprise in the context of digital transformation in order to increase the level of digital maturity of the enterprise. The digital maturity levels of the operating model are considered, followed by an example of a possible distribution of the spectrum of technologies according to these digital maturity levels. The article discusses issues related to the mechanism for implementing digital transformation at industrial enterprises in modern conditions. The article considers the categorical apparatus affecting the management of digital changes: digital transformation, as applied to industry. In addition, the authors highlight the main problem points to which the management of enterprises should pay attention when implementing digital transformation and draw conclusions regarding changes in approaches to organizing the system of interaction within the company. Analytical and expert assessments of project development forecasts using modern digital technologies are used as research methods. The study is based on a comprehensive analysis and subsequent assessment of the main results of the implementation of the processes of technological transformation of projects in industry, followed by the definition of its key areas and directions. In project management in the era of digital transformation, the most applicable approach is one that combines tight control of results on the horizon of strategic planning and inspiring flexibility in organizing work over short distances.